2016
DOI: 10.1111/jpn.12543
|View full text |Cite
|
Sign up to set email alerts
|

Effect of in ovo injection of threonine on immunoglobulin A gene expression in the intestine of Japanese quail at hatch

Abstract: The objective of this study was to investigate the effect of in ovo injection of threonine (THR) on immunoglobulin A (IgA) gene expression of Japanese quail on hatch day. A total of 540 Japanese quail eggs were assigned into nine groups of 60 each and were set in a single-stage incubator. Treatments were as follows: non-injected (control), two diluent levels (0.05 or 0.1 ml saline), two sites of injection (in or under the air sac) and with or without nutrients (0.5 mg/ml THR). Eggs were injected on d 11 of inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The only exception was glycine, which was significantly decreased in urine of the rats in EE and P groups. As the most important amino acid with immunoregulatory effect, threonine can not only stimulate gene express of IgA, but also participant the generation process of immunoglobulin together with serine directly (Kermanshahi et al, 2016;Su et al, 2013). 2-Hydroxybutyrate, the metabolic product of threonine, also was found up-regulated in our results.…”
Section: The Effect Of Ee On Systemic Metabolitessupporting
confidence: 71%
“…The only exception was glycine, which was significantly decreased in urine of the rats in EE and P groups. As the most important amino acid with immunoregulatory effect, threonine can not only stimulate gene express of IgA, but also participant the generation process of immunoglobulin together with serine directly (Kermanshahi et al, 2016;Su et al, 2013). 2-Hydroxybutyrate, the metabolic product of threonine, also was found up-regulated in our results.…”
Section: The Effect Of Ee On Systemic Metabolitessupporting
confidence: 71%
“…The proportion of proline and glycine in the embryo rises with incubation time. Proline is synthesized from many different AAs, whereas the synthesis of glycine is limited to only serine and threonine . In this technique, the injection of AAs on the seventh day of incubation had shown an increase in the BW by 3.6% .…”
Section: Applications Of In Ovo Technology For Various Biological Supmentioning
confidence: 99%
“…Proline is synthesized from many different AAs, whereas the synthesis of glycine is limited to only serine and threonine. 74,75 In this technique, the injection of AAs on the seventh day of incubation had shown an increase in the BW by 3.6%. 72 Injection of arginine (35 mg per egg) and threonine (25 mg per egg) and their mixture into amnion improved feed efficiency and post-hatch growth rate of broilers.…”
Section: Amino Acidsmentioning
confidence: 99%
“…Rezaeipour, Fononi, and Irani (2012) observed that antibody titres of chicks increased as dietary threonine level increased. Increasing dietary threonine levels increased serum IgG concentration in growing pigs (Li et al, 1999) and increased mRNA expression of jejunal IgA in newly hatched chicks (Kermanshahi, Tabari, Emami, Daneshmand, & Ibrahim, 2016). In the current study, IgA and IgG concentrations in colostrum from gilts fed DT were lower compared with colostrum from gilts fed AT or ST, indicating that insufficient threonine intake may limit maternal production of colostral immune globulins.…”
Section: Discussionmentioning
confidence: 99%